A novel and simple torque ripple minimization method of synchronous reluctance machine based on torque function method - Wu, Hailong (Institute of Electrical and Electronics Engineers Inc., 2021)
Synchronous reluctance machine (SynRM) has been studied widely in order to reduce its high torque ripple and improve its low power factor. This article proposes a torque ripple reduction method for SynRM by defining a novel parameter-torque function. With the help of torque function, the optimal currents aiming to compensate torque harmonics are obtained. The advantage of the proposed method is that torque function can be obtained easily and torque ripple reduction can be achieved by a simple control method. For the purpose of verifying the proposed method, both simulations and experiments are performed. Finally, the influence of power supply and parameter uncertainty on the proposed method has also been discussed.